Military justice the rights and duties of soldiers and government - White, Nigel D. 1961- (Edward Elgar Publishing, 2022)
While military law is often narrowly understood and studied as the specific and specialist laws, processes and institutions governing service personnel, this accessible book takes a broader approach, examining military justice from a wider consideration of the rights and duties of government and soldiers engaged in military operations"--